Combined hepatic and adipose tissue transcriptomics highlights circulating NASH biomarkers. (March 2023) - Meroni, M.; De Caro, E.; Chiappori, F.; Longo, M.; Paolini, E.; Mosca, E.; Merelli, I.; Lombardi, R.; Badiali, S.; Maggioni, M.; Orro, A.; Mezzelani, A.; et al.
Abstract : Introduction: Obesity represents the main contributor to nonalcoholic fatty liver disease (NAFLD) and adipose tissue is strongly interlaced with the liver in the disease pathogenesis and progression. Previous studies were restricted to investigate the hepatic transcriptome across the entire spectrum of NAFLD, whereas the transcriptomic changes which occur in white adipose tissue (WAT) in relation to liver damage have been poorly investigated. Aim: Therefore, we aimed to compare hepatic and adipose tissue transcriptome in NAFLD patients with the purpose to identify shared biomarkers useful for the diagnosis of advanced liver damage. Materials and Methods: We performed high-throughput RNA-sequencing in 167 hepatic samples from obese patients and in a subset of 79 matched adipose tissues. Patients were subdivided in normal liver, mild and severe NAFLD according to histology. Circulating cathepsin D (CTSD) was assessed by ELISA. Results: We identified a specific transcriptomic signature that may discriminate patients with severe NAFLD and isolated steatosis, including 424 deregulated genes in liver and 209 in adipose tissue. According to pathway and network analyses, inflammation, ECM remodeling and mitochondrial dysfunction were upregulated whereas oxidative phosphorylation was downregulated in both tissues. We highlighted 13 genes commonly deregulated in both tissues and among them, CTSD showed the most robust diagnostic accuracy in discriminating mild and severe NAFLD. In 52 obese subjects and in a validation cohort of 432 histologically-characterized NAFLD patients, serum CTSD progressively increased from normal liver to severe NAFLD and it was associated with steatosis, necroinflammation, fibrosis, steatohepatitis (NASH) and NAS>5. The area under the curve (AUC) weighted for transaminases to foresee severe NAFLD versus mild and normal liver was 0.78 and 0.87, respectively. Conclusions: CTSD may be a possible biomarker of severe NAFLD since its hepatic/adipose tissue expression as well as circulating levels correlated with liver damage thus allowing to discriminate advanced disease.